Pendidikan Kesehatan Tentang Pola Makan Bergizi dan Seimbang di Era Pandemi Covid-19 Di Wilayah Kerja Puskemas Bantul II - Nur Yeti Syarifah; Siti Uswatun Chasanah (LPPM STIKES Guna Bangsa Yogyakarta, 2021)
One of the Basic Human needs is the need for food which is an important need because it involves the food and drink needed by humans to stay alive. The United Nations Food and Agriculture Agency (FAO) calls for the importance of maintaining a healthy diet during the Covid-19 pandemic. The occurrence of the pandemic causes changes in everyday life. Good nutrition is very important before during and after infection, so to deal with this situation it is necessary to have good health education for the community in the hope that the community will be able to protect their families from the transmission of the corona virus. Health counseling on a nutritious and balanced diet in the Covid 19 pandemic era is expected to help increase the degree of optimal health and increase endurance so that it can prevent the transmission of covid 19.